A review on medical management of inflammatory bowel disease during the coronavirus disease 2019 pandemic. Issue 4 (15th September 2020) - Chela, Harleen; Pasha, Syed Bilal; Wan, Xiu‐Feng; Ghouri, Yezaz A
Abstract: The coronavirus disease 2019 pandemic has engulfed the world and is the highlight of medical community at this time. As humanity fights the battle against this virus, questions are arising regarding the appropriate management of at risk patient populations. The immunocompromised cohort is particularly susceptible to this infection, and we have tried to explore the medical management of one such group, which is composed of individuals with inflammatory bowel disease (IBD). There is limited data on the management of IBD during the ongoing pandemic. Several medical societies have put forth suggestions on how to manage immunocompromised patients in order to minimize risk of developing coronavirus disease 2019. This review aims to present available recommendations from experts and provides an insight on preventive and therapeutic strategies that can be implemented for the medical management of patients with IBD. We anticipate that as more information arises, new guidelines will emerge.